COVID-19 vaccine hesitancy in periconceptional and lactating women: a systematic review and meta-analysis protocol. Issue 11 (7th November 2022) - Su, Xianzhi; Lu, Hua; Li, Xinyun; Luo, Mingli; Li, Fangyuan; Zhang, Qi
Abstract : Introduction: The pandemic of COVID-19 disease has caused severe impact globally. Governments consider vaccination as an effective measure to control pandemic. However, many people have been hesitant to receive COVID-19 vaccine, particularly periconceptional and lactating women. Although research has indicated that pregnant women with COVID-19 are at a higher risk of adverse pregnancy and birth outcomes, as well as severe illness. There appears to be a lack of systematic and comprehensive evidence of the prevalence and determinants of COVID-19 vaccine hesitancy among periconceptional and lactating women. As a result, it has been essential to investigate periconceptional and lactating women's vaccination views and behaviours. This study will review articles on vaccine hesitancy among periconceptional and lactating women to assess the impact of the COVID-19 vaccine hesitancy during the pandemic. Methods and analysis: We will systematically search observational studies from 1 November 2019 to 30 October 2021 in the following databases: Web of Science, PubMed, EMBASE, MEDLINE, Cochrane Library, EBSCO, WHO COVID-19 Database, CNKI and WanFang Database. The following medical subject headings and free-text terms will be used: "COVID-19 vaccines" AND "female" AND "vaccine hesitancy". Eligibility criteria are as follows: population (women of reproductive age); exposure (currently pregnant, lactational or trying to get pregnant); comparison (general women who are not in preconception, gestation or lactation) and outcome (the rate of COVID-19 vaccine hesitancy). Article screening and data extraction will be undertaken independently by two reviewers, and any discrepancy will be resolved through discussion. We will use I 2 statistics to assess heterogeneity and perform a meta-analysis when sufficiently homogeneous studies are provided. We will explore the potential sources of heterogeneity using subgroup and meta-regression analysis. Ethics and dissemination: This study will use published data, so ethical approval is not required. The findings will be disseminated by publication in peer-reviewed journal(s). PROSPERO registration number: CRD42021257511.